Implementasi Model Problem Based Learning Untuk Meningkatkan Keterampilan Sosial - Siwi, Ken; Sutini; Agung Prasetyo (Griya Journal of Mathematics Education and Application, 2025)
This study was motivated by the low level of social skills among students of class VII-B at MTsN 4 Sidoarjo, as indicated by students’ lack of confidence in expressing opinions, limited ability to work collaboratively, and minimal participation in group discussions. Social skills play an important role in the learning process and student interactions; therefore, appropriate instructional strategies are required. This study aimed to determine students’ social skill levels before the implementation of the Problem Based Learning (PBL) model, describe the implementation of PBL in class VII-B, and evaluate its effectiveness in improving students’ social skills. The research employed Classroom Action Research (CAR), consisting of planning, action, observation, and reflection stages. The participants were 31 students of class VII-B. Data were collected using a social skills questionnaire. The results showed that students’ social skills in the pre-cycle phase reached 52.39%, categorized as moderately skilled. After the implementation of PBL, students’ social skills increased to 70.62% in the skilled category in Cycle I and further improved to 85.72% in the very skilled category in Cycle II. In conclusion, Problem Based Learning proved to be effective in improving students’ social skills, including communication, collaboration, and empathy.